Insight into Metastable Lifetime of α‐Calcium Sulfate Hemihydrate in CaCl2 Solution. Issue 10 (14th June 2013) - Jiang, Guangming; Mao, Jingwei; Fu, Hailu; Zhou, Xu; Guan, Baohong; Struble, L.
<x xml:space="preserve">Abstract</x> Alpha calcium sulfate hemihydrate (α‐HH), an important kind of cementitious material, is a metastable phase in CaSO4–H2O system. In CaCl2 solution, thermodynamic metastable window for α‐HH preparation from calcium sulfate dihydrate is constructed as a function of CaCl2 concentration (0–4.0m) and temperature (60°C–130°C), and then the metastability of α‐HH is characterized by the metastable lifetime (MLT). As the concentration of CaCl2 is raised from 1.5 to 4.0m and temperature from 80°C to 110°C, MLT of α‐HH decreases gradually from 2920 to 60 min. The reducing effect of CaCl2 on MLT arises from its contribution to lowering the total interfacial Gibbs free energy required for the subsequent phase transition of α‐HH to anhydrite, the thermodynamic stable phase. This work establishes a method to evaluate the phase metastability and provides a potential approach to optimize the reaction time in metastable material synthesis according to the MLT value for purity control.